Higher education and gross enrolment ratio in India - Saurabh (Innovative Research Thoughts, 2018)
This research paper indicate the status of higher education in India. The status of higher education indicates by the help of table. There is some change on the level of education after the independence. This change may not occur as a direct response to calls for greater transparency and accountability, but rather because of the opportunity to reflect on the purpose of higher education, the role of colleges and universities in the new millennium, and emerging scientific research on how people learn. These disparate literatures have not been tied together in a way that would examine the impact of fundamental change from the policy level to the institutional level and to the everyday lives of college and university administrators, faculty and students. Now the time has come to create a second wave of institution building and of excellence in the fields of education, research and capability building. We need higher educated people who are skilled and who can drive our economy forward. When India can provide skilled people to the outside world then we can transfer our country from a developing nation to a developed nation very easily and quickly. The secondary data for indicate the level of higher education taken from website, books and newspaper.